Advances on a free-piston Stirling engine-based micro-combined heat and power system. (25th November 2022) - Jiang, Zhijie; Yu, Guoyao; Zhu, Shunmin; Dai, Wei; Luo, Ercang
Highlights: Key parameters of a Stirling cogeneration unit were optimized by thermoacoustics. A cogeneration efficiency of 95.7% was achieved in experiments after optimization. The effectiveness of improvement has been validated in experiments. Effect of water temperature difference on cogeneration was studied experimentally. Abstract: As a promising supplement to traditional central electric generation technologies, a distributed combined heat and power (CHP) system is conducive to renewable energy deployment and mitigation of carbon emissions. Among the candidate technologies, the free-piston Stirling engine (FPSE)-based CHP technology is competitive in micro- or small-scale applications. In this work, the performance of a FPSE-based micro-CHP system is improved through a combination of numerical optimization and experimental validation. First, by using a third-order model and thermoacoustic analysis, the impact of regenerator length, displacer moving mass, and force factor of the alternator on the free-piston Stirling generator (FPSG) inside acoustic field, supplied thermal power and exergy loss is studied numerically. The numerical results indicate a rational increase of the force factor, the regenerator length as well as the displacer moving mass is positive for improving the CHP performance. Based on the numerical optimization, the FPSG prototype is updated accordingly, and adequate measurements of the internal acoustic field of the FPSG have been deployed. Then, a series of experiments are conducted to evaluate the CHP performance of the refurbished FPSG prototype. The experimental results show that the highest CHP efficiency reaches 95.7%, the output electric power is 4.03 kW, and the corresponding thermal-to-electric efficiency is 32.2% when the average temperature of supply and return water is as high as 75 °C. Compared with the work before upgrade, the output electric power and CHP efficiency are improved significantly by 39% and 9.4%, respectively. An insight into the impact of the temperature difference between supply and return water indicates that it has a slight impact on electric power generation, especially under higher charge pressure. In contrast, thermal production exhibits an apparent negative correlation with the temperature difference.